2021
DOI: 10.3346/jkms.2021.36.e280
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Excess All-cause Mortality during COVID-19 Pandemic in Korea

Abstract: Background Excess all-cause mortality is helpful to assess the full extent of the health impact, including direct and indirect deaths of coronavirus disease 2019 (COVID-19). The study aimed to estimate overall and regional excess all-cause mortality during the pandemic in Korea. Methods We obtained all-cause death data and population statistics from January 2010 to December 2020. The expected mortality in 2020 was estimated using a quasi-Poisson regression model. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…Figure 6 shows the same situation for the Republic of Korea, which is geographically in the vicinity of these two countries. The result from comparison of the forecast respiratory deaths and actual COVID-19 deaths for the Republic of Korea is align with the results of very recent study about estimation of excess mortality in Korea by Shin et. al., (2021), which shows that the mortality in 2020 was similar to the historical trend.…”
Section: Excess Mortality Analysissupporting
confidence: 88%
“…Figure 6 shows the same situation for the Republic of Korea, which is geographically in the vicinity of these two countries. The result from comparison of the forecast respiratory deaths and actual COVID-19 deaths for the Republic of Korea is align with the results of very recent study about estimation of excess mortality in Korea by Shin et. al., (2021), which shows that the mortality in 2020 was similar to the historical trend.…”
Section: Excess Mortality Analysissupporting
confidence: 88%
“…A modeling study indicates that reported COVID-19 deaths are inadequate to assess the impact of the pandemic on excess mortality [ 14 ]. Excess mortality is a more comprehensive index to measure the impact of the COVID-19 pandemic on deaths, and it refers to the number of deaths from all causes during the pandemic more than what we would have expected to see under “normal” conditions, including the deaths induced by a lack of medical resources and restrictive intervention during the pandemic [ 19 , 20 , 21 ]. Moreover, excess mortality can be the reference for assessing COVID-19 deaths because further studies can estimate COVID-19 deaths based on this result by subtracting other causes of death from excess mortality (e.g., heat waves, war, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This study identified a significantly larger negative excess mortality than previous studies, which estimated an excess mortality close to zero [12,13] and identified positive excess mortality [10,11]. Considering the granularity of the data used in each study, this constitutes an example of the coastline paradox wherein the length of the coastline is measured longer in smaller units.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 64%
“…The preliminary results from the Health Insurance Review and Assessment Service (HIRA) of South Korea reported that observed deaths were within range of the expected mortality during the COVID-19 pandemic period. [13]. The study using vital statistics also identified decreases in the overall mortality.…”
Section: Introductionmentioning
confidence: 89%